What is pneumonia? - Grant Waterer (European Respiratory Society, 2021)
The diagnosis of pneumonia is both simple and complex. Recent research is challenging our concept of pneumonia and radiological gold standards that have underpinned research for decades. In particular, the accuracy of chest radiographs in diagnosing pneumonia is now highly questionable when compared with computed tomography scans. Depending on the question being asked, pneumonia can be defined in clinical, pathological, radiological, or microbiological contexts, or frequently a combination of all of these. However, while the field is changing, until we have new studies defining pneumonia in new ways, clinicians can be reassured that existing guidelines based on “old” standards remain as valid as they have always been.